Thermal conditions in the marine coastal waters as a factor favorable for formation of extra-strong year-classes of Karaginsky pink salmon - Е. А. Shevlyakov; N. А. Dederer; V. I. Ostrovsky; G. V. Khen (Известия ТИНРО, 2024)
Variability of the timing for downstream migration of juvenile pink salmon from the Hailulya River to the adjacent coastal waters of Karaginsky Bay is considered and influence of the coastal water temperature on strength of the year-classes for two generative lines of pink salmon spawning in the Karaginsky Bay is analyzed for 1978–2020. The optimal conditions for the downstream migration in the period after 2002 are determined as the mean weighted per migration intensity water temperature > 5.6 o C (up to 7.8 о С on average with the maximum 9.9 о С in some years) and a stable increasing of the temperature during migration. The factor of food availability for juveniles became less important for formation of the Karaginsky pink salmon year-classes since the late 2000s, in comparison with the temperature. Statistical model is proposed for the year-class strength dependence on the temperature of coastal waters in late June and the parents number (R2 = 0.791). The modeled hindcasts of the pink salmon returns in 2021–2023 were rather satisfactory. Given these new results, the limits of pink salmon escapement to spawning grounds could be reconsidered and fishery management models should be adjusted to modern conditions of unrestricted juvenile feeding to get and rationally exploit super-strong year-classes of this species.